Basic Concepts (Categories) of Sports Theory (Diversity Research: Journal of Analysis and Trends, 2023)
In the process of studying the theory of sports, it is necessary, first of all, to strictly define the concepts that relate to the subject of this discipline. In this article highlights of basic concepts (categories) of sports theory